1990
DOI: 10.1111/j.1464-410x.1990.tb14932.x
|View full text |Cite
|
Sign up to set email alerts
|

Symptoms versus Flow Rates versus Urodynamics in the Selection of Patients for Prostatectomy

Abstract: Many prostatectomies are performed on the basis of symptoms alone; 39% of patients referred by their family doctors and 23% of patients who were on waiting lists for prostatectomy of other hospitals, but who had not undergone any urodynamic investigations, were found to be unobstructed on urodynamic criteria. A screening peak urinary flow rate of 12 ml/s or less was associated with urodynamic evidence of obstruction in 95% of cases; 35% of patients with symptoms of outflow obstruction and a flow rate greater t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0
1

Year Published

1993
1993
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(20 citation statements)
references
References 11 publications
2
17
0
1
Order By: Relevance
“…19 Additionally, McLoughlin et al concluded that a Q max of less than 12 mL/s is a good indicator of outflow obstruction. 20 In the present study, the positive predictive value of Q max for outflow obstruction was 65% at a flow rate of less than 10 mL/s and 100% at a flow rate of less than 5 mL/s. These values were lower than those reported by other researchers.…”
Section: Discussionsupporting
confidence: 46%
“…19 Additionally, McLoughlin et al concluded that a Q max of less than 12 mL/s is a good indicator of outflow obstruction. 20 In the present study, the positive predictive value of Q max for outflow obstruction was 65% at a flow rate of less than 10 mL/s and 100% at a flow rate of less than 5 mL/s. These values were lower than those reported by other researchers.…”
Section: Discussionsupporting
confidence: 46%
“…Although symptoms usually stimulate patients to seek treatment, some studies have shown that there is no correlation between symptoms and bladder outlet obstruction (10,11). Uroflowmetry can be an additional tool for urologists before surgical intervention or treatment failure.…”
Section: Discussionmentioning
confidence: 99%
“…It is well recognized that symptoms are often not reliably associated with outflow obstruction and a poor urinary stream may result from impaired detrusor contractility instead of obstruction, or a normal flow rate could be sustained by a supranormal detrusor pressure. Furthermore, symptom score and peak urinary flow rate are often not in agreement [13][14][15].…”
Section: Introductionmentioning
confidence: 99%